The renewable rise: Shaping Bangladesh's energy future in the context of COP30 - Saihan, Selim; Tiasha, Afia Mubasshira; Pal, Barun Deb (SANEM Publications, 2025)
Globally, climate change disrupts energy systems through extreme weather events, rising sea levels, and shifting resource availability. Increasing temperatures, unpredictable rainfall, and frequent cyclones pose a threat to energy infrastructure in Bangladesh, a low-lying and climate-vulnerable region. These climatic hazards also influence energy consumption patterns and degrade the efficiency of generation systems. As Bangladesh elevates its energy sector to meet development goals, incorporating climate resilience is critical to ensuring long-term sustainability and security. This policy brief outlines the current challenges, reviews government actions, proposes alternative solutions, and assesses their potential economic impacts in the context of Bangladesh’s preparation for the 30th COP in November 2025 and the development of the third Nationally Determined Contribution (NDC).